Effects of inflammatory markers and biographical stress on treatment response in depression. (September 2021) - Block, A.; Schulze, S.; Deeken, F.; Häusler, A.; Rezo, A.; Rapp, M.A.; Wippert, P.M.
Abstract : Background: Recent research emphasized the role of inflammatory processes in the pathophysiology of depression. Theories hypothesizes that life events (LE) can affect the immune system and trigger depressive symptoms. LE are also considered as one of the best predictors for the onset and course of depressive disorders. Methods: Observational study across three treatment settings: n=208 depressive patients (75.5%f, M 46.6 y) were examined on depression (BDI-II), life events (ILE) and inflammatory markers (IL-6, CRP, fibrinogen, ICAM-1, TNF-alpha, E-selectin) at baseline (t0), 5-week(t1) and 5-month(t2) follow-up. Effects and interactions were analyzed with regression models. Results: LE were associated with depressive symptoms at t0 (beta=.209; p=.002) and both follow-ups. Except for CRP, which was linked to depression symptoms at t2 (betai=-.190; p=.032), there were no effects of inflammatory markers on depressive symptoms. At t1, an interaction between CRP and LE in total (beta=-.249; p=.041) was found as well as for LE in the past five years (beta=-.122; p=.027). Similar interactions were found between cumulative LE and ICAM-1 (beta=-.197; p=.003) and IL-6 (beta=-.425; p=.001). Conclusion: The cumulative burden of LE effects symptoms and treatment outcome in depressive patients. There is some evidence that inflammatory marker may have long-term effects on treatment outcome as they seem to weaken the determining relation between LE and depression.